Studies on antifungal properties of plant extracts on mustard blight caused by Alternaria brassicae - and S. GANGOPADHYAY, SURENDRA SINGH*, S. L. GODARA (Indian Phytopathology, 2013)
Plant extracts viz., C. procera, W. somnifera, A. indica leaves, A.indica seed kernel, A. sativum bulband S. suratteuse green berries prepared in distilled water, acetone or methanol significantly inhibited mycelial growth as well as spore germination of A. brassicae. The results showed that the extracts of Azadirachta leaves prepared in distilled water, acetone and methanol were inhibitory to mycelial growth of A. brassicae in PDA and also germination of spores of the fungus. The inhibition of growth and spore germination of the fungus increased with the increase in concentration of the test extracts prepared in all the three solvents. The inhibition was most spectacular when the extracts were used at 15 per cent concentration. Azadirachta seed kernel and Calotropis procera leaf extracts were also highly inhibitory to mycelial growth and spore germination. While, A. sativum, W. somnifera and S. suratteuse were relatively less toxic to it. Field studies conducted under artificial inoculation conditions revealed that two foliar sprays of aqueous extracts (10%) of A. indica seed kernel, C. procera or A. indica leaves suppressed Alternaria blight and enhanced seed yield in mustard.